Разработка автоматизированной системы тестирования большого объема проектов - Лопатина, А. А.; Лавров, А. А. (ХНУРЕ, 2020)
Educational activity, like other spheres of human activity, is subject to changes and modern trends. One of these trends is the desire to fully or partially replace a person with the help of automation, which increases the efficiency of the process of checking students' tasks. One of the relatively new methods of knowledge control is machine control - testing using an automated results verification system. This project proposes to create an automated system for testing projects created with the EDA Playground.
Keywords: EDA Playground; автоматизация тестирования работ; Python